PEMANFAATAN MINYAK PALA DAN MINYAK NILAM PADA EFFLEURAGE MASSAGE DALAM MENURUNKAN NYERI DISMENOREA PADA REMAJA PUTRI DI KOTA BANDA ACEH - Fazlaini, Risna; Frisca Fazira,; Fitria, (Jurnal Medikes (Media Informasi Kesehatan), 2025)
The incidence of menstrual pain among adolescents according to the WHO ranges from 16.8% to 81%. In Indonesia, the prevalence of dysmenorrhea is reported at 107,673 individuals (64.25%), of which 59,671 individuals (54.89%) experience primary dysmenorrhea. In Aceh, the percentage of dysmenorrhea patients visiting the obstetrics department ranges from 1.07% to 1.31%. The treatment of dysmenorrhea has so far mostly involved pharmacological therapy, such as the administration of analgesics. However, analgesic medications can cause side effects such as dependency and withdrawal symptoms. One way to alleviate the intensity of menstrual pain is through effleurage massage using essential oils. The aim of this study was to compare the effectiveness of nutmeg oil and patchouli oil in reducing menstrual pain among adolescents in Banda Aceh. This study used a quantitative research method with a quasi-experimental design, specifically a pretest and posttest design. The study was conducted from August to November 2024. The sample consisted of midwifery students from Bina Bangsa Getsampena University who experienced primary dysmenorrhea. A total of 40 respondents were selected, with 20 respondents in each group. Effleurage massage was performed 1–2 times daily during the first 3 days of menstruation for 15–30 minutes. One group received massage using nutmeg oil, while the other group used patchouli oil.The results showed that both nutmeg and patchouli oils had an effect on the level of dysmenorrhea among adolescents. Statistical analysis using paired t-test and independent t-test showed that effleurage massage using both patchouli oil and nutmeg oil significantly reduced dysmenorrhea intensity among adolescents (p-value < 0.05).